1992
DOI: 10.1007/bf03222843
|View full text |Cite
|
Sign up to set email alerts
|

Superplasticity and superplastic forming of aluminum metal-matrix composites

Abstract: Editor's Note: This article describes the composition of metal·matrix composites using a nomenclature system consisting of five parts: the matrix alloy designation, the reinforcement material, the volume percent of the reinforcement, the morphology of the reinforcement, and the generic temper designation. Under this system, a matrix of aluminum alloy 6061 reinforced with 40 vol. % SiC particulate and given a T6 heat treatment is written as 6061 /SiC/ 4Op-T6. When a matrix/reinforcement system is being discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…At a strain rate of 1 s -1 , a tensile specimen may undergo the adiabatic heating significantly during the deformation, and then strain softening behavior caused by raising the temperature of the specimen may occur. [20][21][22] It was reported that high strain rate superplasticity in aluminum metal-matrix composites occurs in the presence of some liquid, even though the temperature appears to be below the solidus. 22 Because of the high strain rate, the effective temperature is expected to be higher than nominal testing temperature, due to adiabatic heating.…”
Section: Superplastic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At a strain rate of 1 s -1 , a tensile specimen may undergo the adiabatic heating significantly during the deformation, and then strain softening behavior caused by raising the temperature of the specimen may occur. [20][21][22] It was reported that high strain rate superplasticity in aluminum metal-matrix composites occurs in the presence of some liquid, even though the temperature appears to be below the solidus. 22 Because of the high strain rate, the effective temperature is expected to be higher than nominal testing temperature, due to adiabatic heating.…”
Section: Superplastic Propertiesmentioning
confidence: 99%
“…[20][21][22] It was reported that high strain rate superplasticity in aluminum metal-matrix composites occurs in the presence of some liquid, even though the temperature appears to be below the solidus. 22 Because of the high strain rate, the effective temperature is expected to be higher than nominal testing temperature, due to adiabatic heating. Then the effective temperature rises above the solidus line.…”
Section: Superplastic Propertiesmentioning
confidence: 99%
“…Nieh et. al proposed that incipient melting at grain boundaries makes HSRS possible in the 2124-SIC composite [4,5,15], and this idea has been adapted by various workers [7,9,10]. Bieler et al analyzed HSRS of the IN90211 aluminum alloy assuming that a threshold stress resists dislocation motion needed to accommodate grain boundary sliding, and many experimental data of HSRS could be properly interpreted by incorporating threshold stress [18,21].…”
Section: Introductionmentioning
confidence: 98%
“…The value n = 1 represents a viscous flow process [15] and n = 2 is found for the case of superplastic deformation [16]. The case of n = 3 applies to the viscous glide mechanism [17].…”
Section: Introductionmentioning
confidence: 99%